2018
DOI: 10.1371/journal.pone.0198311
|View full text |Cite
|
Sign up to set email alerts
|

GCalignR: An R package for aligning gas-chromatography data for ecological and evolutionary studies

Abstract: Chemical cues are arguably the most fundamental means of animal communication and play an important role in mate choice and kin recognition. Consequently, there is growing interest in the use of gas chromatography (GC) to investigate the chemical basis of eco-evolutionary interactions. Both GC-MS (mass spectrometry) and FID (flame ionization detection) are commonly used to characterise the chemical composition of biological samples such as skin swabs. The resulting chromatograms comprise peaks that are separat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…For example, because replication studies often produce weaker effect sizes than original studies (Simonsohn, 2015; Open science collaboration, 2015), we attempted to enlarge our sample size of mother-offspring pairs as far as was practicable. We also improved the standardization and reproducibility of our chemical analysis pipeline by performing peak detection with open source software and by integrating the alignment algorithm of Stoffel et al (2015) into an R package (Ottensmann et al, 2018). However, these minor modifications appear to have been of little consequence as the effect sizes of colony membership and mother-offspring similarity did not differ systematically between the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because replication studies often produce weaker effect sizes than original studies (Simonsohn, 2015; Open science collaboration, 2015), we attempted to enlarge our sample size of mother-offspring pairs as far as was practicable. We also improved the standardization and reproducibility of our chemical analysis pipeline by performing peak detection with open source software and by integrating the alignment algorithm of Stoffel et al (2015) into an R package (Ottensmann et al, 2018). However, these minor modifications appear to have been of little consequence as the effect sizes of colony membership and mother-offspring similarity did not differ systematically between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting GC-MS data were then processed using OpenChrom (Wenig & Odermatt, 2010) for detection and correction of split peaks. Afterwards, we used GCalignR in R (Ottensmann et al, 2018; R Core Team, 2019) to align the resulting chromatograms by correcting minor shifts in retention times among samples and maximizing the number of shared components.…”
Section: Methodsmentioning
confidence: 99%
“…We compare our alignment results with two existing algorithms: the correlation optimized warping (COW) algorithm [27,28,29] 5 , and the GCalignR algorithm [15]. We investigated many other existing algorithms, however, most are unsuitable to compare with our algorithm -in some of the exiting algorithms the peak alignment module was not designed to be used on its own [30,11]; some algorithms do not have source code available [12]; some requires a specific MATLAB toolbox that we do not own [14,10]; and another built on proprietary software [13].…”
Section: Comparison With Existing Algorithmmentioning
confidence: 99%
“…These authors concluded that due to the complexity of the metabolome, all existing software will require further improvement and researchers are recommended to perform manual checks on the alignment of important biomarkers. More alignment algorithms have been developed since the review papers above [10,11,12,13,14,15], many of these utilising the mass spectral information for alignment. Current alignment algorithms are all based on traditional, symbolic artificial intelligence (AI) techniques, that is, the use of a set of formal, mathematical rules.…”
Section: Introductionmentioning
confidence: 99%
“…The total ion chromatograms were quality checked, de-noised and Savitzky-Golay 146 filtered before peak detection and peak area integration in OpenChrom®. Peaks were 147 then aligned using the R-package 'GCalignR' (Ottensmann et al 2018) prior to statistical 148 analysis. Peaks were tentatively identified by their mass spectra and retention time index 149 based on a C21-C40 n-alkane standard solution (Sigma-Aldrich).…”
Section: Study Species 104mentioning
confidence: 99%